Emerging trends and research hotspots in atopic dermatitis-related itch over the past 10 years: a bibliometric and visual analysis - Wu, Weiyu; Yu, Fubing; Tao, Xiaoli; Yang, Xiongbo; Xue, Xiaoling; Chen, Bangtao (Frontiers in Medicine, 2025)
IntroductionAtopic dermatitis (AD) is a chronic inflammatory skin disorder that causes itching. While numerous studies on AD-related itch exist, a bibliometric analysis has not been performed on this topic. The study aimed to investigate research trends and hotspots in the field of AD-related itch over the last decade.MethodsWe retrieved publications relevant to AD-related itch published from 2014 to 2023, within the Science Citation Index-Expanded of Web of Science Core Collection. We conducted a bibliometric and visual analysis involving annual publications, nations, institutions, journals, authors, co-citation references, and keywords by utilizing VOSviewer, CiteSpace, and the bibliometric online analysis platform.Results and discussionA total of 2534 articles and reviews were retrieved. Overall, the number of publications on AD-related itch has risen steadily over the past decade. The USA was found to be the most influential nation. Simpson et al. were found to be the most prolific author. Over the past 10 years, research has primarily revolved around barrier function, itching mechanism, sensory neurons, and therapeutic drugs for AD. The mechanisms of AD-related itch and advanced drugs are the current research trends. This study can serve as a foundation for further research.